From sectors to functions: producer services, metropolisation and agglomeration forces in the Ile-de-France region - Ludovic Halbert (Belgeo)
This paper reviews the role of producer services in the scientific debate on metropolisation processes and discusses the different types of agglomeration economies. Based on the critical appraisal of sectoral based approaches, it develops a more functional case study of the geography of producer services in the Paris metropolitan region to test the form and nature of economic specialization. The results confirm the multipolar-monocentric pattern which seems to be a common feature in many European cities. The paper concludes on the importance of a functional and hierarchical division of labor in the Paris city-region.